Aux sources britanniques des salles d'asile françaises - Marie Vergnon (Nantes Université, 2023)
In the histories of pre-schooling in France, references to the British infant school are a common thing. Works on the history of early childhood education have shown the plurality of proposals that might have fed the development of French institutions. References to Robert Owen and his infant school, in particular, are already present in the writings of the first organizers of collective early childhood education in France. But the French who went to Great Britain in order to observe the infant schools visited mostly London establishments. It is then appropriate to ask ourselves, by comparing what we know about Owen's Scottish infant school and the projects of the first organizers of collective education for young children in France, what may have traveled of the values and pedagogical projects defended by Owen into the French institutions. The strictly pedagogical dimension, still only slightly studied, allows us here to shed some complementary light to previous work.